Loss of Frizzled 9 in Lung Cells Alters Epithelial Phenotype and Promotes Premalignant Lesion Development - Sompel, Kayla; Dwyer-Nield, Lori D.; Smith, Alex J.; Elango, Alamelu P.; Vanderlinden, Lauren A.; Kopf, Katrina; Keith, Robert L.; Tennis, Meredith A. (Frontiers in Oncology, 2022)
The transmembrane receptor Frizzled 9 (FZD9) is important for fetal neurologic and bone development through both canonical and non-canonical WNT/FZD signaling. In the adult lung, however, Fzd9 helps to maintain a normal epithelium by signaling through peroxisome proliferator activated receptor  (PPAR). The effect of FZD9 loss on normal lung epithelial cells and regulators of its expression in the lung are unknown. We knocked down FZD9 in human bronchial epithelial cell (HBEC) lines and found that downstream EMT targets and PPAR activity are altered. We used a FZD9-/- mouse in the urethane lung adenocarcinoma model and found FZD9-/- adenomas had more proliferation, increased EMT signaling, decreased activation of PPAR, increased expression of lung cancer associated genes, increased transformed growth, and increased potential for invasive behavior. We identified PPAR as a transcriptional regulator of FZD9. We also demonstrated that extended cigarette smoke exposure in HBEC leads to decreased FZD9 expression, decreased activation of PPAR, and increased transformed growth, and found that higher exposure to cigarette smoke in human lungs leads to decreased FZD9 expression. These results provide evidence for the role of FZD9 in lung epithelial maintenance and in smoking related malignant transformation. We identified the first transcriptional regulator of FZD9 in the lung and found FZD9 negative lesions are more dangerous. Loss of FZD9 creates a permissive environment for development of premalignant lung lesions, making it a potential target for intervention.